Evaluation of Positive End-Expiratory Pressure Strategies in Patients With Coronavirus Disease 2019–Induced Acute Respiratory Distress Syndrome - Pan, Chun; Lu, Cong; She, Xiaobin; Ren, Haibo; Wei, Huazhang; Xu, Liang; Huang, Yingzi; Xia, Jia'an; Yu, Yuetian; Chen, Lu; Du, Bin; Qiu, Haibo (Frontiers in Medicine, 2021)
Background: Different positive end-expiratory pressure (PEEP) strategies are available for subjects with coronavirus disease 2019 (COVID-19)–induced acute respiratory distress syndrome (ARDS) requiring invasive mechanical ventilation. We aimed to evaluate three conventional PEEP strategies on their effects on respiratory mechanics, gas exchanges, and hemodynamics. Methods: This is a prospective, physiologic, multicenter study conducted in China. We recruited 20 intubated subjects with ARDS and confirmed COVID-19. We first set PEEP by the ARDSnet low PEEP–fraction of inspired oxygen (FIO2) table. After a recruitment maneuver, PEEP was set at 15, 10, and 5 cm H2O for 10 min, respectively. Among these three PEEP levels, best-compliance PEEP was the one providing the highest respiratory system compliance; best-oxygenation PEEP was the one providing the highest PaO2 (partial pressure of arterial oxygen)/FIO2. Results: At each PEEP level, we assessed respiratory mechanics, arterial blood gas, and hemodynamics. Among three PEEP levels, plateau pressure, driving pressure, mechanical power, and blood pressure improved with lower PEEP. The ARDSnet low PEEP–FIO2 table and the best-oxygenation strategies provided higher PEEP than the best-compliance strategy (11 ± 6 cm H2O vs. 11 ± 3 cm H2O vs. 6 ± 2 cm H2O, p = 0.001), leading to higher plateau pressure, driving pressure, and mechanical power. The three PEEP strategies were not significantly different in gas exchange. The subgroup analysis showed that three PEEP strategies generated different effects in subjects with moderate or severe ARDS (n = 12) but not in subjects with mild ARDS (n = 8). Conclusions: In our cohort with COVID-19–induced ARDS, the ARDSnet low PEEP/FIO2 table and the best-oxygenation strategies led to higher PEEP and potentially higher risk of ventilator-induced lung injury than the best-compliance strategy. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04359251.